2002
DOI: 10.1021/jo010176z
|View full text |Cite
|
Sign up to set email alerts
|

Kulokekahilide-1, a Cytotoxic Depsipeptide from the Cephalaspidean Mollusk Philinopsis speciosa

Abstract: The cytotoxic depsipeptide kulokekahilide-1, which contains two unusual amino acids, 4-phenylvaline and 3-amino-2-methylhexanoic acid, was isolated from the cephalaspidean mollusk Philinopsis speciosa. Structure elucidation of kulokekahilide-1 was carried out by spectroscopic analysis and chemical degradation. The absolute stereochemistry was determined by Marfey analysis for amino acids and chiral HPLC analysis for hydroxy acids. All four stereoisomers of 4-phenylvaline and 3-amino-2-methylhexanoic acid, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
55
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(57 citation statements)
references
References 21 publications
2
55
0
Order By: Relevance
“…2957, 2870, 1738, 1650, 1646, 1538, 1453, 1410, 1385, 1367, 1315, 1279, 1240, 1215, 1186, 1083 cm -1 ; 1 H and 13 C NMR data, see Table 1, assignments were made by interpretation of 2D DQF COSY, edited- Advanced Marfey Analysis. 6 A portion of the acid hydrolysate (0.05 mg) and the standards (2R,3R)-Amha and (2S,3R)-Amha were separately derivatized by treatment with 1 M NaHCO3 (50 µL) and a 1% solution of 1-fluoro-2,4-dinitrophenyl-5-L-alaninamide in acetone (50 µL). After heating at 45°C for 1 h, the reaction mixtures were cooled, acidified with 2 N HCL (25 µL), and diluted with MeCN (100 µL).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…2957, 2870, 1738, 1650, 1646, 1538, 1453, 1410, 1385, 1367, 1315, 1279, 1240, 1215, 1186, 1083 cm -1 ; 1 H and 13 C NMR data, see Table 1, assignments were made by interpretation of 2D DQF COSY, edited- Advanced Marfey Analysis. 6 A portion of the acid hydrolysate (0.05 mg) and the standards (2R,3R)-Amha and (2S,3R)-Amha were separately derivatized by treatment with 1 M NaHCO3 (50 µL) and a 1% solution of 1-fluoro-2,4-dinitrophenyl-5-L-alaninamide in acetone (50 µL). After heating at 45°C for 1 h, the reaction mixtures were cooled, acidified with 2 N HCL (25 µL), and diluted with MeCN (100 µL).…”
Section: Methodsmentioning
confidence: 99%
“…The existence of the uncommon 2-hydroxy-3-methylbutyric acid (Hmba) moiety was revealed by the presence of a broad signal (δ H 5.15, δ C 76.0) corresponding to an R-hydroxymethine proton. 6 The expected cross-peak observed in the COSY spectrum for vicinal coupling between H-47 and H-48 was relatively weak and seen only at the noise level. The small coupling constant of H-47 and the high multiplicity of H-48 contribute to the weak cross-peak seen in the COSY spectrum.…”
mentioning
confidence: 95%
“…Amha (123) occurs in depsipeptides such as guineamide D (135) [132], kulokekahilide-1 [138], malevamide B [139], and the ulongamides A-F [140]. Aoya (124) has been found as constituent of dolastatin 17 (136) [141], and Amoa (125) in guineamide C (137) [132], malevamide C [139], onchidin [142], and ulongapeptin [143] (Figure 4.20).…”
Section: Biosynthesis Of B-amino Acids J139mentioning
confidence: 99%
“…It was found that this type of a-methyl-bamino acid is a crucial component of many biologically active cyclic peptides of marine origin. Representative examples are nodularin [3] and microcystin, [4] which are notorious for their hepatotoxicity, and majusculA C H T U N G T R E N N U N G amide C, [5] dolastatin 11 and 12, [6] and kulokekahilide-1, [7] which are valued for their antifungal and antineoplastic activity.…”
Section: Introductionmentioning
confidence: 99%